Clean water: Rights and remedies under environmental law in Malaysia - Mustafa, Maizatun (2004)
This paper arises out of concern over the growing threat of fresh water shortages in Malaysia due to environmental pollution, and the pressing needs of ensuring that public rights to clean water are safeguarded and remedies be made available and accessible to them. Legal instrument has been known to be an important tool in providing the public a platform for environmental justice. In Malaysia, there already exists a large number of legislation that deal with environmental matters, including that of water, notably the Environmental Quality Act 1974. For this purpose, this paper seeks to examine the various legal resources in Malaysia in order to identify avenues for water rights and remedies available. This paper also seeks to find out whether existing mechanism is sufficient in relation to such rights and remedies thus necessitating its changes, what roles the judiciary can play in promoting and securing these rights, and whether the recognition and implementation of water rights have their place towards promoting good water governance in Malaysia. these are some of the issues to be addressed in this paper.